Determinants of credit ratings: evidence from emerging market economies - Manungo, Tavuya (My University, 2017)
Sovereign credit ratings provide a summary of the economic conditions of a particular country, and are a representation of the ability and willingness of a country to make its debt payments as they fall due. These ratings provide an indication of the cost of borrowing in that country, so a country would like to obtain the highest possible credit rating. These ratings are provided by independent agencies who use their own systems to provide a rating and an outlook. Credit ratings are important as they provide information to investors on the potential investability and access to financial markets of that particular country. The problem found by some literature is the reliability of ratings in emerging markets as investors perceive these markets to be riskier in nature. In this paper, the aim was to identify what the different factors that the two big agencies, Moody’s and Standard and Poor’s use when rating a country. This is done through using a multiple regression model on 5 emerging economies from different continents from 1994 to 2015, based on annual data. The first step was to find out what are the macro-economic variables that have strong correlations with the agencies, and the results show that external balances as a % of GDP and the GDP growth have low correlations with the ratings. The regression analysis also shows that Moody’s takes the inflation rate into consideration when rating a country but Standard and Poor’s does not. The paper also wanted to identify the effects of ratings on markets, and this was done through the effect of ratings on the interest rate spreads. The results show that the rating differential, which was the ratings from Moody’s subtracted from the ratings of Standard and Poor’s, affect the interest rate spreads negatively, therefore a better rating should reduce the spread and have a positive effect on the financial markets.
Research thesis submitted in partial fulfilment of the requirements for the degree Masters of Management in Finance and Investment Faculty of Commerce, Law and Management Wits Business School University of Witwatersrand June 2017
Keywords: Credit ratings--Methodology; Ratings agencies (Finance); Stock exchanges--Developing countries